Development of Natural Fungicidal Agricultural Defensives Using Microbial Glycolipid and Vegetable Oil Blends - Anderson O. de Medeiros; Maria da Gloria C. da Silva; Attilio Converti; Fabiola Carolina G. de Almeida; Leonie A. Sarubbo (Surfaces)
The use of pesticides causes significant environmental problems, which drives the search for natural and non-toxic alternatives. In this study, a glycolipid biosurfactant (BS), produced by the yeast Starmerella bombicola ATCC 22214, was utilized as an active ingredient in natural agricultural defensive blends. The mixtures were tested for their fungicidal potential against phytopathogenic fungi isolated from fruits such as papaya, orange, and banana, demonstrating strong inhibition of fungal growth. The genera Penicillium, Colletotrichum, and Aspergillus were the pathogens present in the deterioration of the fruits used in the experiment. The biosurfactant was produced in a fermenter, yielding 10 g/L and reducing the surface tension to 31.56 mN/m, with a critical micelle concentration (CMC) of 366 mg/L. Blends of BS with oleic acid (T1) and lemongrass oil (T2) were found to be effective in controlling fungi. Additionally, the phytotoxicity of these formulations was assessed using Cucumis anguria (gherkin) seeds, where the blend of BS with castor oil (T4) showed the best performance, promoting seed germination. These results indicate the potential of such mixtures as natural alternatives for fungal control in plants and for application in sustainable agricultural systems.